Multiwall carbon nanotube (MWCNT) as a saturable absorber for generation of high q-factor in erbium doped fiber laser (EDFL) / Siti Nadhirah Mohamed Hassan - Siti Nadhirah, Mohamed Hassan (2016)
In this dissertation, we propose to fabricate a higher mechanical strength, polyvinyl alcohol (PVA), type of host material added to the multiwall carbon nanotubes (MWCNTs) powder to significantly increase the capability of Q-switched cavity to generate high energy pulses. MWCNTs-PVA polymer composites based thin film is sandwiched between two fiber ferrules as a saturable absorber. MWCNTs concentration of 1.25 wt.% in PVA shows a good consistency in generating pulsed laser in Q-switched regime with a maximum repetition rate of 34.3 kHz, shortest pulse width of 3.49 μs, maximum peak power of 11.69 mW and maximum pulse energy of 43.23 nJ, respectively. Then, 1.125 wt.% of MWCNT/PVA-based Q-switched erbium-doped fiber laser (EDFL) incorporating in laser cavity with a tunable bandpass filter (TBPF) as the wavelength mechanism to achieve a broadband tuning range is proposed and demonstrated. The tuning range of the generated Q-switched pulses covered a wide wavelength range of 50 nm, which spanned from 1519 nm to 1569 nm and corresponded to the S- and C-band regions. The highest pulse energy of 52.13 nJ was obtained at an output wavelength of 1569 nm, with a corresponding repetition rate of 26.53 kHz and pulse width of 6.10 μs, at the maximum power of 114.8 mW. The proposed system which integrates a MWCNTs-PVA based thin film as passive saturable absorber is economical, easy to fabricate and compatible for integration in laser cavity.